Análisis de demanda y eficiencia energética en el portador eléctrico del proceso de termofijado en una industria textil. - Gualpa Ayala, Eduardo Santiago (2019)
The present energy demand and efficiency analysis project was carried out in a textile industry located at north to Quito, in order to verify the efficiency of the engines involved in the thermomixer process. An information survey was carried out based on the plate data and power supply conductors of the motors. The analysis was carried out by using electric energy quality analyzers, determining the electrical parameters necessary to obtain the utilization demand, power factor, demand factor, efficiency and total energy, these values were applied in the most efficient engines relevant to the process. The maximum demand that occurs in the whole heatsetting process was also analyzed, with measurement in the main protection, which was compared with the total installed load obtained by the information collected from the plate data, obtaining a favorable percentage of use, through the results of demand recording and in the calculation of electrical efficiency it was possible to show that the nominal useful power of the motors has been affected, due to several rewinding processes that have generated a change in their characteristics. The simulation of change considering high efficiency motors, according to the 60034-2-1 standard, with its same nominal power, generates an energy and economic saving, representative for the industry.